2018
DOI: 10.1021/acscentsci.8b00296
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Tracking of Intracellular Metabolism-Derived Cancer Volatiles via Isotope Labeling

Abstract: Cancer detection relying on the release of volatile biomarkers has been extensively studied, but the individual biochemical processes of the cells from which biogenic volatiles originate have not been thoroughly elucidated to date. Inadequate determination of the metabolic origin of the volatile biomarkers has limited the progress of the scientific and practical applications of volatile biomarkers. To overcome the current limitations, we developed a metabolism tracking approach combining stable isotope labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Thus far, only one study reported on the cancer-specific biochemical origin of VOCs. 44 This goal is very difficult to accomplish as VOCs are produced during metabolic cascades as degradation products of the metabolites directly involved in metabolic pathways, and, consequently, conservative methods are unable to determine the VOCs real metabolic origin. 44 Notwithstanding, some metabolites altered in the PCa group were associated with known biochemical pathways, namely pyruvate metabolism, glycine, serine and threonine metabolism, phenylalanine metabolism and steroid hormone biosynthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, only one study reported on the cancer-specific biochemical origin of VOCs. 44 This goal is very difficult to accomplish as VOCs are produced during metabolic cascades as degradation products of the metabolites directly involved in metabolic pathways, and, consequently, conservative methods are unable to determine the VOCs real metabolic origin. 44 Notwithstanding, some metabolites altered in the PCa group were associated with known biochemical pathways, namely pyruvate metabolism, glycine, serine and threonine metabolism, phenylalanine metabolism and steroid hormone biosynthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In future, this issue can be addressed through volatilomics studies of PCa tissue and fluxomic studies. Fluxomic studies allow the understanding of the metabolic origin of endogenous VOCs by labeling and tracking metabolic precursors (e.g., glucose), throughout the metabolic pathways [ 109 ].…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…To overcome these limitations, lipidomics, driven by the rapid development of mass spectrometry, has been developed and used to achieve outstanding results in recent years (1923). In addition, lipidomic analysis can be complemented by the integration of other functional -omics data, such as transcriptomics, or stable isotope-assisted metabolic labeling to generate a sophisticated framework to get deeper insights into biological processes (24, 25). This combined approach can facilitate mechanistic understanding of the crucial components of the atypical lipid metabolism present in various disease states (22).…”
Section: Introductionmentioning
confidence: 99%